Effects of the falls and fractures clinic as an integrated multidisciplinary model of care in Australia: a pre–post study - Gustavo Duque; Sharon Lee Brennan-Olsen; Fernando Gomez; Carmen Lucia Curcio; Derek Boersma; Steven Phu; Sara Vogrin; Pushpa Suriyaarachchi (BMJ Open)
Objectives Traditionally, the approach to fracture prevention has focused on increasing bone mineral density while typically lacking a combined clinical approach to falls prevention and vice versa. To resolve this gap, we implemented and evaluated a novel combined model of care to the assessment and prevention of osteoporosis and falls in the outpatients setting.Setting Falls and Fractures Clinic (FFC) at Nepean Hospital (Penrith, NSW, Australia).Participants Pre-effects and posteffects assessment of 106 community-dwelling older patients referred from the community.Primary and secondary outcome measures Previous falls and fractures were recorded. Clinical, functional and paraclinical evaluations were performed. A comprehensive multidisciplinary care plan was then tailored based on the presence of risk factors. Six-month follow-ups were performed assessing the incidence of falls and fractures, change in risk factors for falls and level of risk, with the recommended plan.Results We report that 97% of patients had a fall in the preceding 6 months, 47.6% of whom experienced a fracture from the fall. Furthermore, 64% of patients had a marked risk for falling by Physiological Profile Assessment (PPA), 90% had intermediate–high 10-year probability of fracture according to FRAX and 78% had sarcopenia. At 6-month follow-up, we observed more than an 80% reduction in falls and recurrent falls, and 50% reduction in fractures. In addition, 65% of patients had reduced PPA and a 57% reduction in 10-year fracture probability.Conclusions In conclusion, we suggest that a multidisciplinary FFC can provide substantial reductions in falls and fractures for high-risk older people, even over a relatively short 6-month time period. The current model of service provision via traditional falls clinics could be significantly improved by encompassing fracture prevention within the multifactorial approach to interventions.